Discours & écrits sur la coopération de production. - Barré, Raphaël (Paris : Association "Le "Papier", 1900)
Bibliotheek E. Anseele
Dedicator: Barré, Raphaël, dedicatee: Anseele, Edward (sr.)
Frans
Monografie